PENYULUHAN TENTANG PENTINGNYA SENAM HAMIL DAN PERAWATAN PAYUDARA PADA IBU HAMIL TRIMESTER III - Mastikana, Indah; Mutiara, Sherly; Fariningsih, Erika; Hartini Janet Laga, Febri; Nurillah, Sari (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2021)
The purpose of this Community Service Activity is to increase knowledge and attitudes in skills by doing exercise for pregnant women and breast care to prepare for the smooth delivery process and facilitate milk production during breastfeeding. The method used in this Community Service is to disseminate information in the form of counseling about knowledge and practice of pregnancy exercise movement techniques and breast care techniques before delivery and for breastfeeding preparation. Participants in this activity were 7 third trimester pregnant women. The evaluation of this activity is that participants can understand the material presented, it is proven that participants are enthusiastic about asking questions and are willing to directly practice pregnancy exercise techniques and correct breast care techniques. The result of this activity is that there is an increase in knowledge and enthusiasm or care for mothers or participants by participating in counseling activities by doing pregnancy exercises and breast care, seen from the post test results, it was found that participants who had good knowledge and skills increased from the seven people who attended. Most of the participants were aged 23-36 years, with the last education in high school, with all participants being housewives.